Dengue severity by serotype and immune status in 19 years of pediatric clinical studies in Nicaragua. - Federico Narvaez; Carlos Montenegro; Jose G Juarez; José Victor Zambrana; Karla Gonzalez; Elsa Videa; Sonia Arguello; Fanny Barrios; Sergio Ojeda; Miguel Plazaola; Nery Sanchez; Daniel Camprubí-Ferrer; et al. (PLoS Neglected Tropical Diseases)
Background Dengue virus, a major global health threat, consists of four serotypes (DENV1-4) that cause a range of clinical manifestations from mild to severe and potentially fatal disease. Methods This study, based on 19 years of data from the Pediatric Dengue Cohort Study and Pediatric Dengue Hospital-based Study in Managua, Nicaragua, investigates the relationship of serotype and immune status with dengue severity. Dengue cases were confirmed by molecular, serological, and/or virological methods, and study participants 6 months to 17 years old were followed during their hospital stay or as ambulatory patients. Results We enrolled a total of 15,833 participants, of whom 3,308 (21%) were positive for DENV infection. Of 2,644 cases with serotype result by RT-PCR, 559 corresponded to DENV1, 1,002 to DENV2, 760 to DENV3 and 323 to DENV4. Severe disease was more prevalent among secondary DENV2 and DENV4 cases, while similar disease severity was observed in both primary and secondary DENV1 and DENV3 cases. According to the 1997 World Health Organization (WHO) severity classification, both DENV2 and DENV3 caused a higher proportion of severe disease compared to other serotypes, whereas DENV3 caused the greatest percentage of severity according to the WHO-2009 classification. DENV2 was associated with increased odds of pleural effusion and low platelet count, while DENV3 was associated with both hypotensive and compensated shock. Conclusions These findings demonstrate differences in dengue severity by serotype and immune status and emphasize the critical need for a dengue vaccine with balanced effectiveness against all four serotypes, particularly as existing vaccines show variable efficacy by serotype and serostatus.